2014
DOI: 10.5897/ajar11.036
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of soil fertility status under different crop cultivation in Gombe

Abstract: A comparative study was conducted among three different cropping areas. Samples were collected from each area and are taken to laboratory for analysis, and variables such as organic carbon, available phosphorous, total nitrogen, PH, electrical conductivity, particle size distribution, exchangeable bases and CEC were tested. The statistical analysis is used to obtain the mean values of the result obtained from each variable. A fertility rating score was design using the evaluation key to determine the fertility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…To improve the quality and fertility level of the soils in these locations, Onwudike et al (2016) recommended urgent need to adopt strategic management measures and agronomic principles that will improve the fertility levels. Likewise, in a study reported by Aliyu and Ray (2014), on the comparative study of soil fertility rating under crop cultivation in Gombe, it was reported that under groundnut farm, available phosphorous rated as moderately low has the mean value of 29 ppm which scores three marks, while organic carbon, exchangeable Na, Ca, and CEC are rated as very low. This variable has the mean of values 0.85, 0.88, 4.93 and 6.25 respectively which scored two marks.…”
Section: 1mentioning
confidence: 90%
“…To improve the quality and fertility level of the soils in these locations, Onwudike et al (2016) recommended urgent need to adopt strategic management measures and agronomic principles that will improve the fertility levels. Likewise, in a study reported by Aliyu and Ray (2014), on the comparative study of soil fertility rating under crop cultivation in Gombe, it was reported that under groundnut farm, available phosphorous rated as moderately low has the mean value of 29 ppm which scores three marks, while organic carbon, exchangeable Na, Ca, and CEC are rated as very low. This variable has the mean of values 0.85, 0.88, 4.93 and 6.25 respectively which scored two marks.…”
Section: 1mentioning
confidence: 90%
“…It is bounded to the north by Kwami local government area, to the south and west by Akko, and to the East by Yamaltu-Deba. 13 It has a projected population of about 400,000 in 2010. 14 (Fig.…”
Section: Study Areamentioning
confidence: 99%